2007
DOI: 10.1086/513006
|View full text |Cite
|
Sign up to set email alerts
|

η Carinae across the 2003.5 Minimum: Spectroscopic Evidence for Massive Binary Interactions

Abstract: We have analyzed high spatial, moderate spectral resolution observations of Eta Carinae (η Car) obtained with the Space Telescope Imaging Spectrograph (STIS) from 1998.0 to 2004.3. The data were obtained at discrete times covering an entire 2024 day spectroscopic cycle, with focus on the Xray/ionization low-state which began in 2003 June. The spectra show prominent P-Cygni lines in H I, Fe II and He I which are complicated by blends and contamination by nebular emission and absorption along the line-of-sight t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
164
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(179 citation statements)
references
References 45 publications
14
164
1
Order By: Relevance
“…Studies of the binary or binary wind-wind collision zone were reported by many authors (e.g., Damineli 1996;Damineli et al 1997Damineli et al , 1998Damineli et al , 2000Damineli et al , 2008bDavidson 1997;Davidson et al 2005Davidson et al , 2015Smith & Gehrz 2000;Smith et al 2004;Smith 2010;Pittard & Corcoran 2002;Corcoran et al 1997Corcoran et al , 2001Corcoran 2005;Ishibashi et al 1999;Soker 2003Soker , 2007Weis et al 2005;Gull et al 2006Gull et al , 2009Gull et al , 2011Gull et al , 2016Nielsen et al 2007;Weigelt et al 2007; Kashi & Soker 2007, 2009aParkin et al 2009;Groh et al 2010Groh et al , 2012bMadura & Owocki 2010;Madura et al 2012Madura et al , 2013Mehner et al 2010aMehner et al , 2011Mehner et al , 2012Mehner et al , 2015Richardson et al 2010;Teodoro et al 2013Teodoro et al , 2016Clementel et al 2015a,b;Hamaguchi et al 2016). The X-ray...…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the binary or binary wind-wind collision zone were reported by many authors (e.g., Damineli 1996;Damineli et al 1997Damineli et al , 1998Damineli et al , 2000Damineli et al , 2008bDavidson 1997;Davidson et al 2005Davidson et al , 2015Smith & Gehrz 2000;Smith et al 2004;Smith 2010;Pittard & Corcoran 2002;Corcoran et al 1997Corcoran et al , 2001Corcoran 2005;Ishibashi et al 1999;Soker 2003Soker , 2007Weis et al 2005;Gull et al 2006Gull et al , 2009Gull et al , 2011Gull et al , 2016Nielsen et al 2007;Weigelt et al 2007; Kashi & Soker 2007, 2009aParkin et al 2009;Groh et al 2010Groh et al , 2012bMadura & Owocki 2010;Madura et al 2012Madura et al , 2013Mehner et al 2010aMehner et al , 2011Mehner et al , 2012Mehner et al , 2015Richardson et al 2010;Teodoro et al 2013Teodoro et al , 2016Clementel et al 2015a,b;Hamaguchi et al 2016). The X-ray...…”
Section: Introductionmentioning
confidence: 99%
“…The second component is probably a late-type nitrogen-rich O or Wolf-Rayet (WR) star (Iping et al 2005;Verner et al 2005). The semi-major axis of the orbit is 16.64 AU (Hillier et al 2001) and the eccentricity is very high (e ∼ 0.9, Nielsen et al 2007). Thus, the periastron distance r periastron is around 1.66 AU, while the primary star's radius R ,1 , although poorly constrained, is estimated to be in the range 0.7-1 AU (respectively, Corcoran & Hamaguchi 2007;Damineli 1996).…”
Section: Introductionmentioning
confidence: 99%
“…• (e.g., Moffat & Corcoran 2009;Okazaki et al 2008;Henley et al 2008;Hamaguchi et al 2007;Nielsen et al 2007;Gull et al 2011;Madura 2010;Madura et al 2011Madura & Groh 2012;Parkin et al 2009). Some other papers claim an opposite view, namely ω ≃ 90…”
Section: Introductionmentioning
confidence: 99%